Evaluation of optimal conditions for arginase activity in streptozotocin-induced diabetic rats - Erytyr, M; Erçel, E; Yilmaz, S; Ozan, ST (Wiley, 2005)
[Abstract Not Available]
30th Congress of the Federation-of-European-Biochemical-Societies (FEBS)/9th IUBMB Conference -- JUL 02-07, 2005 -- Budapest, HUNGARY